TAX AMNESTY DALAM PERSPEKTIF SYARIAH: TINJAUAN TERHADAP KEPATUHAN DAN PENERIMAAN PAJAK - Dara, Dara Fauzia; Rusmanti Fisabililah, Endah; Nirmalawati, Syifa; Cassena, Dewuwuh; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
Taxes are Indonesia's main source of revenue to support government operations and the implementation of development programs. However, the level of compliance of individual taxpayers in Indonesia is still low, which can hinder the success of national development which is highly dependent on tax revenue. To overcome this problem, the government implements a Tax Amnesty policy that provides forgiveness of fines and sanctions for tax evaders to increase tax compliance. This study aims to analyze Islam's views on taxes and Tax Amnesty policies, as well as their impact on tax compliance in Indonesia. This study uses a descriptive qualitative method with a literature study as the main data source. The results of the study show that the Tax Amnesty policy is designed to expand the tax database and encourage tax compliance in the future. From the Sharia perspective, taxes are allowed as long as they are aimed at the benefit of the people, with the application of the principle of justice in their imposition and use. Tax compliance is considered important to increase state revenue and support the sustainability of national development.